YOGA THERAPY AND DISABILITY - Belia Méndez Rial (Federación Extremeña de Balonmano; University of Extremadura, 2015)
Yoga is a useful supportive intervention for a broad range of pain-associated diseases. It is often recommended as therapy for a variety of medical conditions and it is rising popularity as therapy (Verrastro, 2014). Yoga is a system of movement and breathing exercises meant to foster mind-body connection. It creates inner, physical and emotional balance through the use of postures, called asanas, combined with breathing techniques or pranayama (Posadzki et al, 2011). Benefits are found in different areas: Physical benefits (e.g.: flexibility, coordination, strength, endurance) mental benefits (e.g.: to develop greater awareness, diminish anxiety and reduction of distress, positive behavioural changes, improvement mood, facilitate positive emotions and optimism, broaden cognitive processes and enhance self- efficacy for pain control) or social (e.g.: to reduce isolation, to foster social networks and reinforce social support). Researches show that even despite persistent pain symptoms, patients recognize that they are able to be physically active, they experience higher self-competence and self-awareness, which contributes to higher quality of life. Moreover, yoga therapy is a safe and beneficial supportive treatment, relatively cheap, it requires just the motivation of patients (Posadzki et al, 2011; Büsing et al, 2012) and a good professional support. Objectives: The aim of this review it is to determine what are the topics of the researches about Yoga therapy and disability.